The Mathematics Learning Aided by Android Applications and Its Impact: A Mixed Methods Study - Laswadi, Laswadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2022)
The rapid development of technology in various fields requires us to adapt and incorporate it into our daily lives and the world of education. However, it is necessary to conduct research and identify appropriate applications to ensure technology is used effectively in learning. This study aims to uncover junior high school students' experiences using an Android-based application, namely Algebra Tiles, and determine the impact of using such applications on the students’ learning outcomes in mathematics. The students reflected on their experiences while participating in mathematics classes in eleventh-grade at one of the junior high schools in Kerinci, Jambi, Indonesia. An embedded design of a mixed methods approach, combining qualitative and quantitative methods, was employed to understand students' experiences and learning effectiveness. Interviews and observations were conducted to reveal how the students interacted with the application during the learning process. In addition, a concept comprehension test was administered to students who learned with the assistance of the Android application and to a comparison group who learned without it. The data obtained through observations and interviews were subjected to thematic analysis. On the other hand, the data from the student's comprehension test results were analyzed using statistical methods. The research findings indicate that students who learned with the assistance of the Android application achieved higher concept comprehension scores than those who learned without it. Multi-directional communication between students and teachers, as well as between students themselves, was observed to be very active. There was a transition in the focus of discussions from technical issues with the application during the initial meetings to issues related to learning materials in subsequent meetings. However, signs of boredom were observed in the final two meetings. Overall, the students expressed enthusiasm and felt challenged to explore what could be learned using the Android-based application. The active interactions among students through verbal communication during the learning process indicate that the application can potentially enhance students' engagement in mathematics learning.